Organização e racionalidade: o caso da indústria da moda - Vanessa Alves Justino (2007)
Based on organizations Sociology, the fashion industry and its specifications were analyzed in relation to other kinds of industries. The analyses focus privileges discussions concerning the actors build up, and the processes that explain their actions and decisions in an organizational context. Ive noticed that in the fashion industrys productive chain, the stylist configures himself as a strategic actor. Although his image is related to one like a talented free creator genius, as of an artistuncompromised with reality, his creations would come in fact, from his capacity to conceal objective factors, that inhibit his creations like, for instance, the clients and the companys characteristics, with his works creative side. One of the peculiarities in fashion industry is the uncertainty factor and risk, in which the decisions are involved. The universe here investigated reaches seven stylists that act on the fashion market in the state of Espírito Santo, as well as a specific bibliography in thissector.